66.6k views
4 votes
Given the 2 following functions: h(x) = 2x-3 k(x) = -5x2 + 2x - 4 Writing your answer in standard form what would the coefficient be of the second term of h(x)×k(x)?

User Osaxma
by
5.8k points

1 Answer

4 votes

You have the following functions:

h(x) = 2x - 3

k(x) = -5x² + 2x - 4

To determine the coefficient of the second term of h(x)*k(x), calculate this product:

h(x)*k(x) =

(2x - 3)(-5x² + 2x -4) =

(2x)(-5x²) + (2x)(2x) + (2x)(-4) + (-3)(-5x²) + (-3)(2x) + (-3)(-4) =

-10x³ + 4x² - 8x + 15x² - 6x + 12 =

-10x³ + 19x² - 14x + 12

Hence, the coefficient of the second term is 19

User Lams
by
6.2k points